PENGARUH KETIDAKPUASAN, VARIETY SEEKING, DAN BRAND IMAGE TERHADAP BRAND SWITCHING DARI SMARTPHONE ANDROID KE IPHONE - Pulasari, Gede Nanda Dharmawan; Raka Sukawati, Tjokorda Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
Brand switching is a buying pattern marked by the shift of consumers from one brand to another which is influenced by various factors including dissatisfaction, variety seeking, and brand image. The purpose of this study is to explain the effect of dissatisfaction, variety seeking, and brand image on brand switching from Android smartphones to Iphones. This research design uses an associative research design with a causal relationship. This research was conducted in Denpasar City, the number of samples used were 100 respondents who were iPhone smartphone users who had previously moved from Android smartphones in the last 3 years with a non-probability sampling method with purposive sampling technique. Answers from respondents were collected and then analyzed using multiple linear regression analysis techniques. The results of this study indicate that dissatisfaction has a positive and significant effect on brand switching. Variety seeking has a positive and significant effect on brand switching. Brand image has a positive and significant effect on brand switching.